Molothrus bonariensis (Gmelin, 1789) (Passeriformes: Icteridae) is a threat to the cuban biological diversity - Olivera-Bacallao, Damaris (2023)
Invasive species are animals, plants, or other organisms transported and introduced by humans in places outside their natural distribution area and that have managed to establish and disperse in the new region, where they are harmful. The objective of the research was aimed to propose a system of workshops to contribute to the knowledge of Invasive Exotic Species (IES), and their undesirable effects on vulnerable Cuban ecosystems and in particular on the bird species Molothrus bonariensis (Gmelin, 1789), 8th-graduate students of the Basic Urban Secondary School "Fe del Valle". For the effective development of this research, methods of information gathering and processing were used in their dialectic interrelation, which allowed us to verify fy existing deficiencies in terms of knowledge of IES and their undesirable effects. The research represents a novel way of appropriating new knowledge about M. bonariensis among the 8th-grade students studying in that school. In order to mitigate the difficulties detected, the workshop system was developed and submitted to the criteria of experts who evaluated it as pertinent. With the implementation of the system, it was possible to verify the progress achieved by the schoolchildren in the knowledge of M. bonariensis as an IES.